2021
DOI: 10.1111/cdev.13689
|View full text |Cite
|
Sign up to set email alerts
|

When judging what you know changes what you really know: Soliciting metamemory judgments reactively enhances children’s learning

Abstract: Wanlin Zhao and Baike Li contributed equally to the present study.The data contained in this project and the pre-registration of Experiment 2 are publicly available at the Open Science Framework (OSF) at https://osf. io/7gcwp/.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 71 publications
3
24
0
Order By: Relevance
“…Importantly for the current research, together these findings suggest that JOL reactivity for word pairs depends on item relatedness. Further, other studies observed positive JOL reactivity for recall or recognition of single words (Double et al, 2018;Halamish, 2018;Senkova & Otani, 2021;Tekin & Roediger, 2020;Zhao et al, 2021) but no reactivity with educationally-relevant materials (Ariel et al, 2021). Given that JOL reactivity and its direction depend on the type of studied materials, it is imperative to examine the potential effect of JOLs on recall with various types of materials in order to develop a comprehensive theory of JOL reactivity (Myers et al, 2020).…”
mentioning
confidence: 99%
“…Importantly for the current research, together these findings suggest that JOL reactivity for word pairs depends on item relatedness. Further, other studies observed positive JOL reactivity for recall or recognition of single words (Double et al, 2018;Halamish, 2018;Senkova & Otani, 2021;Tekin & Roediger, 2020;Zhao et al, 2021) but no reactivity with educationally-relevant materials (Ariel et al, 2021). Given that JOL reactivity and its direction depend on the type of studied materials, it is imperative to examine the potential effect of JOLs on recall with various types of materials in order to develop a comprehensive theory of JOL reactivity (Myers et al, 2020).…”
mentioning
confidence: 99%
“…Mitchum et al (2016) proposed that making concurrent JOLs might borrow limited cognitive resources from the primary learning task, leading to a weaker encoding of temporal information. In addition, frequent task-switching between encoding and monitoring might also induce dual-task costs and lead to negative reactive influences (for related discussion, see Janes et al, 2018; Zhao et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In a recent meta-analysis, Double et al (2018) found that making item-by-item JOLs significantly enhances memory for at least some types of materials 1 . For instance, previous studies found that eliciting JOLs facilitates retention of related word pairs and word lists (Soderstrom et al, 2015; Zhao et al, 2022), whereas it has minimal influence on memory for unrelated word pairs (Double et al, 2018) or text passages (Ariel et al, 2021). Other studies found that the reactivity effect occurs in young children (Zhao et al, 2022) as well as young adults, although making JOLs fails to facilitate older adults’ memory (Tauber & Witherby, 2019).…”
Section: Reactivity Effectsmentioning
confidence: 99%
See 2 more Smart Citations